COUNTERFACTUAL HISTORICAL NARRATION IN HISTORICAL FICTION: MICHAEL KLEEBERG’S DREAM OF ALTERNATIVE GERMANY - İbrahim ÖZBAKIR (Fırat University, 2019)
Among the radical changes and developments experienced in the second half of the 20th century, novel is the one which was most affected of all the literary genres and as one of the non-dogmatic genres it experienced a process parallel to that of the development of artistic creation. With the announcement of the end of the grand narratives and the breakdown of the belief in truths, historical narratives began to lose its characteristic of being based on a document and history has been recognized as a fiction of writer. Trying to demonstrate that history and novel share the same literacy methods, literary theorists pointed out especially the similarity of their narrative forms. The postmodern novel, which is interested in history and which problematizes history while using it, eliminated familiar boundaries between literature and history. In this article, it has been tried to illustrate how this was carried out in Michael Kleeberg’s work, “Ein Garten im Norden” which is one of those presenting a counterfactual reality, while producing alternatives to history.